Comparison of biochemical responses between top-ten and lower placed road cyclists to a six-day stage race - Lee, H.; Martin, D. T.; Bannan, S.; Boston, T.; Anson, J.; Hahn, A. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Preliminary studies have characterised the effects of multi-day stage racing on discrete aspects of blood biochemistry in road cyclists. However, no studies to date have examined whether these changes differ in magnitude between successful competitors and those placing further back in the field. Fourteen Australian road cyclists participating in the "1998 Tour of Tasmania" agreed to donate blood on the morning of each race day (D1-D6). Venous blood (8 ml) was collected between 6:30 and 8:00 AM via venepuncture of a superficial forearm vein. Blood serum was separated and analysed for: Creatine Kinase (CK), Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), Lactate Dehydrogenase (LD), Urea and Urate (UA) using a Hitachi 911 analyser (Boehringer Mannheim, Tokyo, Japan). Comparisons were made between top10 (Top10) and lower placed (Non-top10) competitors. Data were analysed using a 2 x 6 (group x day) ANOVA and the Newman - Keuls post hoc test was applied where appropriate. Data are presented as Mean± SD with significance recognised when P<0.05. On D1 (baseline) Top10 and Non-top10 were not significantly different for CK (175± 88 vs 109± 28 U/L), ALT (22± 3 vs 16± 3 U/L), Urea (6.2± 0.8 vs 5.8± 1.3 mM) and UA (0.26± 0.4 vs 0.27± 0.4 mM), but were different for AST (29± 5 vs 21± 1 U/L) and LD (262± 37 vs 236± 25 U/L). For both Top10 and Non-Top10 groups there was a significant increase from D1 values for LD ( 23% and 13%), Urea ( 29% and 47%) and UA ( 22% and 21%). Interestingly, significant increases (D1 to peak) in CK ( 103%), ALT ( 48%) and AST ( 38%) were observed only in the Top10 cyclists. These data indicate that changes in serum enzymes in response to successive days of stage racing can be different between highly-placed and other competitors. This may reflect the extra effort required to achieve a top 10 placing in a multi-day stage race.